Mapping the O-GlcNAc Modified Proteome: Applications for Health and Disease - Burt, Rajan A.; Alghusen, Ibtihal M.; John Ephrame, Sophiya; Villar, Maria T.; Artigues, Antonio; Slawson, Chad (Frontiers in Molecular Biosciences, 2022)
O-GlcNAc is a pleotropic, enigmatic post-translational modification (PTM). This PTM modifies thousands of proteins differentially across tissue types and regulates diverse cellular signaling processes. O-GlcNAc is implicated in numerous diseases, and the advent of O-GlcNAc perturbation as a novel class of therapeutic underscores the importance of identifying and quantifying the O-GlcNAc modified proteome. Here, we review recent advances in mass spectrometry-based proteomics that will be critical in elucidating the role of this unique glycosylation system in health and disease.